Answer:
![\large\boxed{4.\ S_{13}=260}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B4.%5C%20S_%7B13%7D%3D260%7D)
![\large\boxed{5.\ \sum\limits_{k=1}^7(2k+5)=91}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B5.%5C%20%5Csum%5Climits_%7Bk%3D1%7D%5E7%282k%2B5%29%3D91%7D)
![\large\boxed{6.\ a_1=17,\ a_2=26,\ a_3=35}](https://tex.z-dn.net/?f=%5Clarge%5Cboxed%7B6.%5C%20a_1%3D17%2C%5C%20a_2%3D26%2C%5C%20a_3%3D35%7D)
Step-by-step explanation:
4.
We have:
![a_6=18,\ a_{13}=32](https://tex.z-dn.net/?f=a_6%3D18%2C%5C%20a_%7B13%7D%3D32)
These are the terms of the arithmetic sequence.
We know:
![a_n=a_1+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29d)
Therefore
![a_6=a_1+(6-1)d\ \text{and}\ a_{13}=a_1+(13-1)d\\\\a_6=a_1+5d\ \text{and}\ a_{13}=a_1+12d\\\\a_{13}-a_6=(a_1+12d)-(a_1+5d)\\\\a_{13}-a_6=a_1+12d-a_1-5d\\\\a_{13}-a_6=7d](https://tex.z-dn.net/?f=a_6%3Da_1%2B%286-1%29d%5C%20%5Ctext%7Band%7D%5C%20a_%7B13%7D%3Da_1%2B%2813-1%29d%5C%5C%5C%5Ca_6%3Da_1%2B5d%5C%20%5Ctext%7Band%7D%5C%20a_%7B13%7D%3Da_1%2B12d%5C%5C%5C%5Ca_%7B13%7D-a_6%3D%28a_1%2B12d%29-%28a_1%2B5d%29%5C%5C%5C%5Ca_%7B13%7D-a_6%3Da_1%2B12d-a_1-5d%5C%5C%5C%5Ca_%7B13%7D-a_6%3D7d)
Substitute a₆ = 18 and a₁₃ = 32:
![7d=32-18](https://tex.z-dn.net/?f=7d%3D32-18)
<em>divide both sides by 7</em>
![d=2](https://tex.z-dn.net/?f=d%3D2)
![a_6=a_1+5d](https://tex.z-dn.net/?f=a_6%3Da_1%2B5d)
![18=a_1+5(2)](https://tex.z-dn.net/?f=18%3Da_1%2B5%282%29)
<em>subtract 10 from both sides</em>
![8=a_1\to a_1=8](https://tex.z-dn.net/?f=8%3Da_1%5Cto%20a_1%3D8)
The formula of a sum of terms of an arithmetic sequence:
![S_n=\dfrac{a_1+n_1}{2}\cdot n](https://tex.z-dn.net/?f=S_n%3D%5Cdfrac%7Ba_1%2Bn_1%7D%7B2%7D%5Ccdot%20n)
Substitute a₁ = 8, a₁₃ = 32 and n = 13:
![S_{13}=\dfrac{8+32}{2}\cdot13=\dfrac{40}{2}\cdot13=20\cdot13=260](https://tex.z-dn.net/?f=S_%7B13%7D%3D%5Cdfrac%7B8%2B32%7D%7B2%7D%5Ccdot13%3D%5Cdfrac%7B40%7D%7B2%7D%5Ccdot13%3D20%5Ccdot13%3D260)
===========================================
5.
We have
![\sum\limits_{k=3}^7(2k+5)\to a_k=2k+5](https://tex.z-dn.net/?f=%5Csum%5Climits_%7Bk%3D3%7D%5E7%282k%2B5%29%5Cto%20a_k%3D2k%2B5)
Calculate ![a_{k+1}](https://tex.z-dn.net/?f=a_%7Bk%2B1%7D)
![a_{k+1}=2(k+1)+5=2k+2+5=2k+7](https://tex.z-dn.net/?f=a_%7Bk%2B1%7D%3D2%28k%2B1%29%2B5%3D2k%2B2%2B5%3D2k%2B7)
Calculate the difference:
![a_{k+1}-a_k=(2k+7)-(2k+5)=2k+7-2k-5=2](https://tex.z-dn.net/?f=a_%7Bk%2B1%7D-a_k%3D%282k%2B7%29-%282k%2B5%29%3D2k%2B7-2k-5%3D2)
It's the arithmetic sequence with first term
![a_1=2(1)+5=2+5=7](https://tex.z-dn.net/?f=a_1%3D2%281%29%2B5%3D2%2B5%3D7)
and common difference d = 2.
The formula of a sum of terms of an arithmetic sequence:
![S_n=\dfrac{2a_1+(n-1)d}{2}\cdot n](https://tex.z-dn.net/?f=S_n%3D%5Cdfrac%7B2a_1%2B%28n-1%29d%7D%7B2%7D%5Ccdot%20n)
Substitute n = 7, a₁ = 7 and d = 2:
![S_7=\dfrac{2(7)+(7-1)(2)}{2}\cdot7=\dfrac{14+(6)(2)}{2}\cdot7=\dfrac{14+12}{2}\cdot7=\dfrac{26}{2}\cdot7=(13)(7)\\\\S_7=91](https://tex.z-dn.net/?f=S_7%3D%5Cdfrac%7B2%287%29%2B%287-1%29%282%29%7D%7B2%7D%5Ccdot7%3D%5Cdfrac%7B14%2B%286%29%282%29%7D%7B2%7D%5Ccdot7%3D%5Cdfrac%7B14%2B12%7D%7B2%7D%5Ccdot7%3D%5Cdfrac%7B26%7D%7B2%7D%5Ccdot7%3D%2813%29%287%29%5C%5C%5C%5CS_7%3D91)
===========================================
6.
We have:
![a_1=17,\ a_n=197,\ S_n=2247](https://tex.z-dn.net/?f=a_1%3D17%2C%5C%20a_n%3D197%2C%5C%20S_n%3D2247)
The formula for the n-th term of an arithmetic sequence:
![a_n=a_1+(n-1)d](https://tex.z-dn.net/?f=a_n%3Da_1%2B%28n-1%29d)
The formula of the sum of terms of an arithmetic sequence:
![S_n=\dfrac{2a_1+(n-1)d}{2}\cdot n](https://tex.z-dn.net/?f=S_n%3D%5Cdfrac%7B2a_1%2B%28n-1%29d%7D%7B2%7D%5Ccdot%20n)
Substitute:
![(1)\qquad 197=17+(n-1)d\\\\(2)\qquad2247=\dfrac{(2)(17)+(n-1)d}{2}\cdot n](https://tex.z-dn.net/?f=%281%29%5Cqquad%20197%3D17%2B%28n-1%29d%5C%5C%5C%5C%282%29%5Cqquad2247%3D%5Cdfrac%7B%282%29%2817%29%2B%28n-1%29d%7D%7B2%7D%5Ccdot%20n)
Convert the first equation:
<em>subtract 17 from both sides</em>
Substitute it to the second equation:
![2247=\dfrac{34+180}{2}\cdot n\\\\2247=\dfrac{214}{2}\cdot n](https://tex.z-dn.net/?f=2247%3D%5Cdfrac%7B34%2B180%7D%7B2%7D%5Ccdot%20n%5C%5C%5C%5C2247%3D%5Cdfrac%7B214%7D%7B2%7D%5Ccdot%20n)
<em>divde both sides by 107</em>
![21=n\to n=21](https://tex.z-dn.net/?f=21%3Dn%5Cto%20n%3D21)
Put the value of n to the equation (n - 1)d = 180:
![(21-1)d=180](https://tex.z-dn.net/?f=%2821-1%29d%3D180)
<em>divide both sides by 20</em>
![d=9](https://tex.z-dn.net/?f=d%3D9)
Therefore we have the explicit formula for the nth term of an arithmetic sequence:
![a_n=17+(n-1)(9)\\\\a_n=17+9n-9\\\\a_n=9n+8](https://tex.z-dn.net/?f=a_n%3D17%2B%28n-1%29%289%29%5C%5C%5C%5Ca_n%3D17%2B9n-9%5C%5C%5C%5Ca_n%3D9n%2B8)
Put n = 1, n = 2 and n = 3:
![a_1=9(1)+8=9+8=17\qquad\text{CORRECT :)}\\\\a_2=9(2)+8=18+8=26\\\\a_3=9(3)+8=27+8=35](https://tex.z-dn.net/?f=a_1%3D9%281%29%2B8%3D9%2B8%3D17%5Cqquad%5Ctext%7BCORRECT%20%3A%29%7D%5C%5C%5C%5Ca_2%3D9%282%29%2B8%3D18%2B8%3D26%5C%5C%5C%5Ca_3%3D9%283%29%2B8%3D27%2B8%3D35)